ANALYSIS OF NOX AIR QUALITY AT INTER-CITY BUS TERMINAL OF NORTH SULAWESI PROVINCE IN 2023 - Akili, Rahayu H.; Punuh, Maureen Irene; Maino, Irny Evita; Sefle, Gandhy (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Intercity bus terminals are a significant source of air pollution, particularly nitrogen oxide (NOx) emissions. NOx emissions frequently reach hazardous levels due to excessive vehicle activity, particularly diesel-powered buses, both when idling and accelerating. Long operational duration, high vehicle density during rush hour, and the age of the bus fleet, which is often older than other public vehicles, all have an impact on NOx emission levels. Long-term NOx pollution exposure has a direct influence on health, namely respiratory system diseases such as lung function and respiratory tract infections. Traders, passengers, and those residing near the terminal are all at greater risk of health complications. The study aimed to assess air quality using nitrogen oxide (NOx) measures. To describe the quality of nitrogen oxide air, this method employs an observational descriptive approach based on direct measurements. The investigation was carried out at the Malalayang and Paal Dua bus terminals. Measurements were obtained twice, in the morning and afternoon, with a 6-point scale. Univariate data analysis shows the minimum, maximum, and average values of the research variables. Research Results: The results of the study at the Malalayang terminal at point 2 which is located in the inner part at 11.42 - 12.41 WITA, the measurement results were 5.50 µḡ / nm³, total volume 22.542 nm³ and at the Paal Dua terminal at point 1, at 10.00 - 11.10 WITA, the measurement results were 6.05 µḡ / nm³ with a total volume of 22,475 nm³. Conclusion: The levels of nitrogen oxide (NOx) at the Malalayang and Paal Dua terminals remain below the quality standard set by Indonesian Government Regulation Number 22 of 2021, which supervises the implementation of environmental protection and management with a 1-hour exposure time.